(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
This paper aims to present a complete analysis of the finds of Hispanic-Roman coinage from the archaeological site of Valeria deposited in the Museum of Cuenca, both the stored ones and the exhibited ones. Firstly, with the novelties in currency copies disclosed we intend to enhance the information available about the Hispanic Provincial coinage found in the territory of the city. Secondly, we will try to clarify some data related to the Hispanic currency supply of the city during the final years of the Roman Republic and the early Empire times, based on fundamental issues, such as periods of minting, the monetary values and, particularly, the mints.